The Love My Breast Android Application as Educational and Early Detection of Cancer - Maratus Sholichah Fitriah Hajar Kusnianto; Wimar Anugrah Romadhon; Handayani (STIKes Patria Husada Blitar, 2025)
Breast cancer is one of the leading causes of death in women worldwide. Lack of information and awareness about women's health problems results in delays in early detection, diagnosis, and treatment, and worsens the prognosis. In this digital era, practical and flexible educational media are needed as an effort to increase public knowledge. This study aimed to analyze the effectiveness of educational media and early detection of breast cancer through the use of the Love My Breast Android application in women of childbearing age. The method was Research and Development (RnD). The population was women of childbearing age (20-49 years). The sampling technique used purposive sampling. In this study, there were two test groups: a limited trial group of 10 respondents and 30 respondents in the broad trial group with Wilcoxon Signed Rank test Analysis. The instruments used the Love My Breast Android application as an educational medium and a questionnaire to measure respondents' attitudes, knowledge, and behavior. The results of this study obtained the application is suitable for use as an educational medium and early detection of Breast Self-Examination. Based on the data, the Love My Breast Android application educational media is effective in increasing respondents' knowledge, attitudes, and behavior. Early detection is an effort to identify abnormalities or diseases that are not yet clinically apparent. The development of easy, practical, and flexible application media is necessary in this digital era to support proactive and preventative efforts in health issues, particularly breast cancer.